Analisis Daya Tampung Beban Pencemar Biochemical Oxygen Demand (Bod) dan Chemical Oxygen Demand (COD) di Sungai Tembuku Kota Jambi Menggunakan Model QUAL2KW - Freddy Ilfan; Lailal Gusri; Winny L.C.H; Citra Rebekka Maulina Siregar (Jurnal Daur Lingkungan, 2022)
Tembuku River is one of the tributaries of Batanghari River in Jambi City which is located across Thehok Village to Simpang Lampu Merah Sijenjang-Pasar Kasang. Tembuku River has the highest pollution level compared to other tributaries with the BOD value of the upstream is 38,5 mg/l and downstream is 86 mg/l, the COD value of the upstream is 42,5 mg/l, and the downstream is 95 mg/l. This research was conducted to analyze the pollutant Load Capacity of Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) that can be received by Tembuku River using Qual2kw model. Qual2kw model is a recommendation model from Peraturan Menteri Negara Lingkungan Hidup no. 1 Tahun 2010 Tentang Tata Laksana Pengendalian Pencemaran Air to calculate the capacity of pollutant load. Based on the research and analysis, the result of pollutant load capacity in Tembuku River is the BOD parameter has 180,9216 kg/day in segment 1, 62,6249 kg/day in segment 2, and 319,3344 kg/day in segment 3, for COD parameter the pollutan load capacity is 815,4432 kg/day in segment 1, 103,52448 kg/day in segment 2, and 1699,7471 kg/day in segment 3. So the value of pollutant load capacity in all parameters and each segment has positive value stating the value of pollutant load capacity can be received by Tembuku River.